2016
DOI: 10.3852/14-346
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of microfungi in peatlands originated from the White Sea

Abstract: The diversity of culturable filamentous microfungi in peat and sediments of four peatlands at the coastal zone of Kandalaksha Bay of the White Sea (Murmansk region, Russia) was studied by culture methods on standard and selective media. Annually 100 samples were collected from the bogs 2007-2010. Based on morphological, molecular markers and cultural features, 211 taxa were identified. Fungal communities observed at the peatlands were influenced mostly by their sea origin. We discovered a large difference betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Natural Y. lipolytica W29 yeast dwells in oily habitats, namely some food (cheese, yogurt, and sauces), wastewater contaminated with oils, as well as marine and hyper-mineralized sources [35,36]. Alkali-and halo-tolerance properties [1] make this organism a very promising model for biotechnological use [37]. In the present study, we could confirm the Y. lipolytica yeast's successful resistance to alkaline stress (pH ≥ 8.0).…”
Section: Discussionsupporting
confidence: 60%
“…Natural Y. lipolytica W29 yeast dwells in oily habitats, namely some food (cheese, yogurt, and sauces), wastewater contaminated with oils, as well as marine and hyper-mineralized sources [35,36]. Alkali-and halo-tolerance properties [1] make this organism a very promising model for biotechnological use [37]. In the present study, we could confirm the Y. lipolytica yeast's successful resistance to alkaline stress (pH ≥ 8.0).…”
Section: Discussionsupporting
confidence: 60%
“…To date, there have been a limited number of articles reporting the microbial composition of tropical peat swamp forests (Boonyuen et al 2012;Bunterngsook et al 2010;Hadi et al 2012;Jackson et al 2009;Pinnoi et al 2006;Posa et al 2011) and temperate and boreal peatlands (Dedysh et al 2006; GrumSection Editor: Eckhard Thines Electronic supplementary material The online version of this article (doi:10.1007/s11557-016-1205-9) contains supplementary material, which is available to authorized users. Grzhimaylo et al 2016;Kachalkin and Yurkov 2012;Kachalkin et al 2008;Thormann et al 2007). Among these, only a few articles have reported yeasts in peatlands of Canada and Russia, and their ecological roles are largely unknown (GrumGrzhimaylo et al 2016;Kachalkin and Yurkov 2012;Kachalkin et al 2008;Thormann et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…We hypothesized that such a transitional ecosystem would contain a unique composition of fungal biodiversity. Earlier studies on typical terrestrial peatlands in the same area showed a drastically different set of fungi (GrumGrzhimaylo and Bilanenko 2012;Bilanenko and GrumGrzhimaylo 2016;Grum-Grzhimaylo et al 2016). Thus, our current study highlights the unusual hydrology of the lake, which in turn has resulted in the establishment of a specific fungal community.…”
Section: Discussionmentioning
confidence: 67%
“…The same analysis was conducted for dominant fungal species in order to verify identification by morphological characters. Total genomic DNA (gDNA) was extracted from the mycelium of the 109 fungal strains using the chloroform/isopropanol method (Karakousis et al 2006;Grum-Grzhimaylo et al 2016). We amplified and sequenced the ITS rDNA for all strains and LSU rDNA for the most of them using common primer sets.…”
Section: Fungal Isolation Cultivation Identification and Data Analysismentioning
confidence: 99%